Prevalence of hypertension and its association with obesity among school children of Pune city, Maharashtra, India: a cross sectional study - Ghonge, Swati; Patel, Hemant S.; Nagar, Shaileshkumar K.; Thakor, Nilesh (International Journal of Research in Medical Sciences, 2017)
Background:There are numerous psychological, physical and economic consequences of obesity. Conditions such as type 2 diabetes mellitus, hypertension and hypercholesterolemia, which were noted primarily in adults, are becoming more common among children with the increase in the prevalence of obesity. The objective of the study was to find out prevalence of hypertension and its association with obesity among school children. Methods: The present cross sectional study was undertaken during July 2009 to April 2011 in randomly selected 4 schools of Pune city. Total 1281 children between the age group of 10 to 15 years were examined after taking written informed consent of their parents using pre-designed, pre-tested, semi-structured performa. Anthropometric measurements were taken and BMI were calculated. The prevalence of overweight and obesity were determined based on the IOTF (International Obesity Task Force) criteria. Blood pressure was measured in the left arm to the nearest 1 mmHg using an electronic machine (Omron Corporation Tokyo, Japan), with the participant seated in a relaxed position. Thus collected data was analyzed using Microsoft Excel and Open- Epi Software. (Version 2.3) Results: Out of 1281 children, 54.09% were males. Overall prevalence of obesity and overweight was 5.62% and 9.99% respectively. Overall, amongst 200 obese and overweight children identified, prevalence of hypertension was 6% and that of pre hypertension was 4.5% as compared to 1.25% and 1.5% ,respectively among the normal weight children. Mean MAC (Mid Upper Arm Circumference) of obese and overweight was 24.8 cm and that of Normal weight children, was 19.1cm with standard deviations of 2.8 and 2.4 cm, respectively. Average Waist-Hip ratio of obese and overweight was 0.87 and that of normal weight children, was 0.80. Mean SBP (Systolic Blood Pressure) of obese and overweight was 111 mm Hg and that of normal weight children was 107 mm of Hg. Mean DBP (Diastolic Blood Pressure) of obese and overweight was 73 mm of Hg and that of normal weight was 69 mm of Hg. Conclusions: Anthropometric measurements like Waist Hip Ratio, MAC and mean SBP and DBP among obese and overweight group of children were significantly higher as compared to normal weight group of children.